2013
DOI: 10.1007/s13191-013-0278-2
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Palatal Rugae Carving in Complete Dentures

Abstract: Palatal rugae play an important role in the production of palato lingual sounds. A simple inexpensive method for carving palatal rugae in complete dentures has been described here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Similar method of customizing rugae of a maxillary complete denture using waxed dental floss and standardizing the thickness of the dental floss to less than a millimeter was carried out by authors. [13][14] The results obtained from the present study for PAT, showed the least amount of articulatory errors in terms of percentage with the customized rugae dentures. The distortions were maximum, followed by substitutions which were mainly for dentoalveolar and fricatives, influenced by the position of tongue, tooth and surface of the anterior portion of hard palate.…”
Section: Discussionmentioning
confidence: 74%
“…Similar method of customizing rugae of a maxillary complete denture using waxed dental floss and standardizing the thickness of the dental floss to less than a millimeter was carried out by authors. [13][14] The results obtained from the present study for PAT, showed the least amount of articulatory errors in terms of percentage with the customized rugae dentures. The distortions were maximum, followed by substitutions which were mainly for dentoalveolar and fricatives, influenced by the position of tongue, tooth and surface of the anterior portion of hard palate.…”
Section: Discussionmentioning
confidence: 74%
“…2 A few attempts have been made to modify the palatal contours of maxillary dentures to produce the desired "normal" speech. These methods include capturing of the palatal rugae by tin foil, 6 interdental floss, 7 palatograms, 1,5,8,9 plastic palate forms, corrugated metal plate, 10 putty impresssion and free hand wax carving. All these techniques attempt to replicate the patient's palatal anatomy but the resulting denture base is not precise and even in thickness.…”
Section: Discussionmentioning
confidence: 99%
“…An overly thick denture prosthesis in the region of anterior palate hampers appropriate formation of palato-lingual sounds. 19 Allen advocated making the palatal portion as thin as is practical. 20 The three major factors that affect the phonetics among complete denture wearers are palatal contour, positioning of the artificial teeth, and vertical dimension of occlusion.…”
Section: Discussionmentioning
confidence: 99%